1994
DOI: 10.2307/2297978
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Investment Models and the Firm's Financial Policy

Abstract: In this paper we investigate the sensitivity of investmentto the availabilityof internal funds usingthe hierarchy of finance approach to corporate finance. Wecharacterizethe empirical implications of this approach for dynamic investmentmodels and test these implications using firm-level data. The model we estimate is based on the Euler equation for optimal capital accumulation in the presence of convex adjustment costs. The theoretical model explicitly allows for debt finance and financial assets.The empirical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

18
649
1
13

Year Published

2001
2001
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 790 publications
(688 citation statements)
references
References 29 publications
18
649
1
13
Order By: Relevance
“…A number of previous studies have found evidence that increased liquidity availability generally impacts positively on fixed capital investment (e.g. Bond & Meghir, 1994;Fazzari, Hubbard, & Petersen, 1988). Some other works and, in particular, the empirical evidence suggest that financial pressure affects employment (Benito & Hernando, 2002;Bond & Meghir, 1994;Bond & Van Reenen, 2007;Cantor 1990;Nickell & Nicolitsas 1999;Sharpe 1994).…”
Section: Theoretical Frameworkmentioning
confidence: 98%
See 1 more Smart Citation
“…A number of previous studies have found evidence that increased liquidity availability generally impacts positively on fixed capital investment (e.g. Bond & Meghir, 1994;Fazzari, Hubbard, & Petersen, 1988). Some other works and, in particular, the empirical evidence suggest that financial pressure affects employment (Benito & Hernando, 2002;Bond & Meghir, 1994;Bond & Van Reenen, 2007;Cantor 1990;Nickell & Nicolitsas 1999;Sharpe 1994).…”
Section: Theoretical Frameworkmentioning
confidence: 98%
“…Bond & Meghir, 1994;Fazzari, Hubbard, & Petersen, 1988). Some other works and, in particular, the empirical evidence suggest that financial pressure affects employment (Benito & Hernando, 2002;Bond & Meghir, 1994;Bond & Van Reenen, 2007;Cantor 1990;Nickell & Nicolitsas 1999;Sharpe 1994). As suggested by Modigliani & Miller (1958) there is no association between a firm's financial structure and its value, implying that a firm's financing choice has no effect on its real operation.…”
Section: Theoretical Frameworkmentioning
confidence: 98%
“…Le capital se déprécie à chaque période t du montant 8K tl et s'accroît du niveau de l'investissement brut. La dépréciation est supposée constante dans le temps (comme Bond et Meghir, 1995).…”
Section: Françaisesunclassified
“…De plus, pour estimer les paramètres du modèle, les variables anticipées en début de période, non observées, sont remplacées par leurs valeurs réalisées ex post (rationalité des anticipations Hayashi, 1985). Dans le premier cas (absence de coûts de transaction et de contrainte d'endettement), on retrouve l'équation d'Euler obtenue sous l'hypothèse de maximisation du profit dans un contexte de perfection du marché du capital (Bond et Meghir, 1995) c'est-à-dire on obtient la relation suivante 1 :…”
Section: Françaisesunclassified
“…In order to obtain data at constant prices, CD it has been deflated using st PY (the by-industry production deflator from NA, see e.g. Bond and Meghir, 1994):…”
mentioning
confidence: 99%